A rapid review of emergency department interventions for children and young people presenting with suicidal ideation. Issue 2 (4th March 2022) - Virk, Farazi; Waine, Julie; Berry, Clio
Abstract : Background: Suicidal ideation is an increasingly common presentation to the paediatric emergency department. The presence of suicidal ideation is linked to acute psychiatric hospital admission and increased risk of suicide. The paediatric emergency department plays a critical role in reducing risk of suicide, strengthening protective factors and encouraging patient engagement with ongoing care. Aims: This rapid review aims to synthesise evidence on interventions that can be implemented in the paediatric emergency department for children and adolescents presenting with suicidal ideation. Method: Six electronic databases were searched for studies published since January 2010: PubMed, Web of Science, Medline, PsycINFO, CINAHL and Cochrane. Outcomes of interest included suicidal ideation, engagement with out-patient services, incidence of depressive symptoms, hopelessness, family empowerment, hospital admission and feasibility of interventions. The Cochrane risk-of-bias tool was used to evaluate the quality of studies. Results: Six studies of paediatric emergency department-initiated family-based ( n = 4) and motivational interviewing interventions ( n = 2) were narratively reviewed. The studies were mainly small and of varying quality. The evidence synthesis suggests that both types of intervention, when initiated by the paediatric emergency department, reduce suicidal ideation and improve patient engagement with out-patient services. Family-based interventions also showed a reduction in suicidality and improvement in family empowerment, hopelessness and depressive symptoms. Conclusions: Paediatric emergency department-initiated interventions are crucial to reduce suicidal ideation and risk of suicide, and to enhance ongoing engagement with out-patient services. Further research is needed; however, family-based and motivational interviewing interventions could be feasibly and effectively implemented in the paediatric emergency department setting.